Analisis Penentuan Strategi Bersaing pada Bisnis Usaha Kafe Omah Koempoel - Iftikar, Muhamad Zaki; Utama, Afwan Syahru; Rahmadhi, Nanda Supraba; Yuananto, Muhammad Naufal; Pratama, Reyhan Atallah Syah; Wardani, Salsabilah Herman Putri (Fakultas Ekonomi dan Bisnis, 2022)
Omah Koempoel is one of the cafes in Batu Tourism City that has many customers because it provides a natural and contemporary cafe concept through neatly arranged joglo-joglo buildings. Because it has many competitors and must be able to satisfy every customer who comes, Omah Koempoel needs to find a strategy to help win the cafe business in Batu Tourism City. The method that used in this study is a strategic management matrix formulation consisting of 3 stages or stages, namely the Input Stage with the Internal Factor Evaluation (IFE) Matrix and the External Factor Evaluation (EFE) Matrix; the Matching Stage using Internal External Matrix (IE) analysis, and the Decision Stage using the QSPM Matrix (Quantitative Strategic Planning Matrix). The results of this study get alternative strategies that Omah Koempoel can use is a development strategy by expanding its market share, expanding business locations, expanding business in other sectors, finding suitable and appropriate locations for the establishment of new businesses, maximizing digital media that is currently developing this, as well as being more active and aggressive in promoting the products offered.